THE MEDIATING ROLE OF GOOD CORPORATE GOVERNANCE ON THE EFFECTS OF LIQUIDITY AND FIRM GROWTH ON DIVIDEND POLICY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2019 TO 2021 - El Badry, Aminatud Dawa'a; Mardi; Ulupui, I Gusti Ketut Agung (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
The determination of an appropriate dividend policy is influenced by various internal and external factors, including a company's financial health, growth prospects, and governance practices. In recent years, scholars and practitioners have shown a growing interest in understanding the intricate relationship between dividend policy and factors such as liquidity, company growth, and corporate governance. This study aims to examine the effect of liquidity and company growth on dividend policy mediated by good corporate governance in manufacturing companies listed on the Indonesia Stock Exchange. The research method used is quantitative with secondary data obtained by compiling annual financial reports from the Indonesian Stock Exchange website. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021. The sample selection used a purposive sampling technique which amounted 111 samples. The data analysis technique in this study is path analysis used SmartPLS software. The results showed that liquidity had a significant negative effect on dividend policy, company growth had no effect on dividend policy, liquidity had a significant negative effect on good corporate governance, company growth had a significant positive effect on good corporate governance, good corporate governance had a significant positive effect on dividend policy, good corporate governance is able to mediate liquidity on dividend policy in a negatively significant, and good corporate governance is able to mediate company growth on dividend policy in a positively significant.